Analisis Proses Produksi Pembuatan Engsel Pintu Mobil Menggunakan Metode PDCA di PT. XYZ - Ahmad Shalihudin; Kardiman Kardiman; Aa Santosa (Peneliti.net, 2022)
From observations on the company's production process in making Hing door through several processes including the stamping process to packing. Those in the production process experience damage to the machine or an error. This study aims to suppress the problem of defects in standard machine conditions, especially on press machines before production. It is proven that after the approach with PDCA, namely the making of SOPs for replacing materials on each machine and adding an identity to the material, it has reduced the proportion of rejections on stamping machines by 74%.